Perovskite Solar Cells: Patterned Wettability Surface for Competition‐Driving Large‐Grained Perovskite Solar Cells (Adv. Energy Mater. 25/2019). Issue 25 (5th July 2019) - Wang, Yang; Li, Mingzhu; Li, Huizeng; Lan, Yangjie; Zhou, Xue; Li, Chang; Hu, Xiaotian; Song, Yanlin
Abstract : In article number1900838, Mingzhu Li, Yanlin Song and co‐workers report a competitive perovskite grain growth approach via a micro‐contact print (MicroCP) method with CD discs as templates for printing a wettability‐patterned substrate, to achieve a large‐grained perovskite and avoid discontinuous perovskite films caused by the low wettability of substrates, resulting in efficiencies over 20% for the MicroCP perovskite solar cells.